2015
DOI: 10.1037/fam0000089
|View full text |Cite
|
Sign up to set email alerts
|

Stress in romantic relationships and adolescent depressive symptoms: Influence of parental support.

Abstract: It is well known that stressful life events can play a role in the development of adolescent depressive symptoms; however, there has been little research on romantic stress specifically. The relationship between romantic stress and depressive symptoms is particularly salient in adolescence, as adolescence often involves the onset of dating. This and other stressors are often dealt with in the context of the family. The present study examined the relationship between romantic stress and depressive symptoms both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
6
32
0
Order By: Relevance
“…Clearly the research on crush experiences during early adolescence would benefit from considering additional psychological outcomes, both concurrently and longitudinally. Thus, the present study extends past research by considering the concurrent and prospective associations between other-sex crush experiences during early adolescence and two psychological outcomes: loneliness and depressive symptoms, two of the most commonly considered outcomes in peer relations and romantic experience research (e.g., Anderson, Salk, & Hyde, 2015; Woodhouse, Dykas, & Cassidy, 2012). …”
Section: Introductionsupporting
confidence: 55%
“…Clearly the research on crush experiences during early adolescence would benefit from considering additional psychological outcomes, both concurrently and longitudinally. Thus, the present study extends past research by considering the concurrent and prospective associations between other-sex crush experiences during early adolescence and two psychological outcomes: loneliness and depressive symptoms, two of the most commonly considered outcomes in peer relations and romantic experience research (e.g., Anderson, Salk, & Hyde, 2015; Woodhouse, Dykas, & Cassidy, 2012). …”
Section: Introductionsupporting
confidence: 55%
“…Parental support and internalizing symptoms. Results demonstrated that maternal support, but not paternal support, was associated with increased internalizing symptoms in college students, consistent with previous work (Anderson et al, 2015). Mothers are often more involved in day-to-day activities throughout development (Lamb, 2002;Lewis et al, 1981).…”
Section: Predictors Of Internalizing Symptoms During Collegesupporting
confidence: 85%
“…These results highlight the importance of exploring the influence of different sources of support separately, and suggest that improving self-esteem for both men and women, and improving maternal support for women may decrease risk for internalizing symptoms in emerging adulthood. exception) and that maternal versus paternal support may play a more important role in protecting children from internalizing symptoms (Anderson, Salk, & Hyde, 2015). In addition, there may be differences in the levels of parental support perceived by men versus women.…”
Section: The Effects Of Parental Support and Self-esteem On Internalimentioning
confidence: 99%
“…In addition to separating parents from other sources of support, it may be beneficial to explore the differences in the amount and function of support from mothers versus fathers. Evidence has suggested that mothers often provide higher levels of support compared to fathers (Furman & Buhrmester, 1992;Phares, Renk, Duhig, Fields, & Sly, 2009;see Colarossi & Eccles, 2000 for an exception) and that maternal versus paternal support may play a more important role in protecting children from internalizing symptoms (Anderson, Salk, & Hyde, 2015). In addition, there may be differences in the levels of parental support perceived by men versus women.…”
Section: Parental Supportmentioning
confidence: 99%